Taxonomy of the freshwater crabs of Costa Rica, with a revision of the genus Ptychophallus Smalley, 1964 (Crustacea: Decapoda: Pseudothelphusidae) - Magalhães, Célio; Wehrtmann, Ingo S.; Lara, Luis Rólier; Mantelatto, Fernando L. (Zootaxa, 2015)
The taxonomy and geographic distribution of the freshwater crabs of the family Pseudothelphusidae Ortmann, 1893, of Costa Rica, Central America, particularly of the genus Ptychophallus Smalley, 1964, are revised. Historical materials deposited in major collections of several institutions were examined, as well as valuable collections in the Zoological Museum of the University of Costa Rica that include abundant specimens obtained recently (2007–2010) in the southern region of the country. The pseudothelphusids of Costa Rica consists of 15 currently valid species belonging to Achlidon Smalley, 1964 (two species), Allacanthos Smalley, 1964 (two species), Potamocarcinus H. Milne Edwards, 1853 (three species), and Ptychophallus (eight species). Two species seem to be restricted to the Atlantic drainage, while seven are known only from the Pacific drainage; six species occur in both drainages. Ptychophallus comprises 13 valid species; four new synonymies are proposed: P. osaensis Rodríguez, 2001, P. campylus Pretzmann, 1968, P. tumimanus ingae            Pretzmann, 1978, and P. barbillaensis Rodríguez & Hedström, 2001, as junior synonyms of P. paraxantusi (Bott, 1968), P. tristani (Rathbum 1896), P. tumimanus (Rathbun, 1898), and P. uncinatus Campos & Lemaitre, 1999, respectively. Two species, P. colombianus (Rathbun, 1896) and P. exilipes (Rathbun, 1898), are considered species inquerendae. Lectotype designations are made for P. montanus and P. colombianus. Three species of Ptychophallus are known exclusively from Costa Rica, five exclusively from Panama, and five species occur in both countries; one species appears to be exclusive of the Atlantic drainage, whereas five are known only from the Pacific drainage and seven occur in both drainages. The gonopod morphology of all species is redescribed and illustrated, and maps of their geographic distribution are furnished. A key to the species of Pseudothelphusidae from Costa Rica and to all species of Ptychophallus is provided.